"It Encourages Family Discussion": A Mixed-Methods Examination of the This Is Us Alzheimer's Disease & Caregiving Storyline. Issue 6 (3rd June 2022) - Hoffman, Beth L.; Sidani, Jaime E.; Wang, Yunwen; Chang, Jonah; Burke, Jessica G.
Abstract : The average United States (U.S.) adult spends approximately one hour interacting directly with a healthcare professional but 2, 000 hours watching primetime television annually. Thus, television storylines may be a powerful vehicle for promoting awareness about Alzheimer's disease and caregiving, which affect an estimated 9 million U.S. adults. We used a mixed-methods approach consisting of an online survey of U.S. adult This Is Us viewers (n = 720) and 4 focus groups (n = 12) with a subset of survey respondents to systematically assess viewer perceptions of an Alzheimer's disease and caregiving storyline from the This Is Us television show and the storyline's influence on viewer behavioral intent toward planning for aging. Triangulation of survey and focus group results suggests the storyline may motivate viewers to discuss plans for aging with their family because of a reduction in stigma and seeing on-screen family tensions related to senior care. Results suggest investments in collaborative partnerships between public health and the entertainment industry may be a valuable way to positively impact those affected by Alzheimer's disease and caregiving. Clips from this storyline could also be used as part of health communication campaigns to encourage advanced care planning discussions.